The Prevalence of Insomnia Subtypes in Relation to Demographic Characteristics, Anxiety, Depression, Alcohol Consumption and Use of Hypnotics - Bjorøy, Ingrid; Jørgensen, Vilde Aanesland; Pallesen, Ståle; Bjorvatn, Bjørn (Frontiers in Psychology, 2020)
Objective: The aim of the present study was to examine the prevalence of insomnia subtypes in relation to several demographic characteristics, as well as to investigate the prevalence of possible anxiety and depression, alcohol consumption and use of hypnotics within the different insomnia subtypes. Methods: The present study was based on an extensive web-based survey made publicly available in 2012. The data was downloaded in January 2019, after 113 887 people had responded to parts of, or the entire questionnaire. The 64 503 participants who met the criteria for chronic insomnia disorder according to the Diagnostic and Statistical Manual of Mental Disorders, fifth edition (DSM-5) comprised the study population. The present study divided insomnia into seven subtypes based on type of sleep difficulty reported; sleep onset insomnia (SOL-insomnia), sleep maintenance insomnia (WASO-insomnia), early morning awakening insomnia (EMA-insomnia) and combinations of these. Data were analyzed with chi-square tests and logistic regression analyses adjusted for sex, age, level of education and marital status. Results: More than 60% of the study population met the criteria of either SOL-insomnia or a mixed insomnia subtype consisting of SOL-, WASO- and EMA-insomnia (SOL+WASO+EMA-insomnia). The percentage distribution of insomnia subtypes within the demographic characteristics showed that participants with female sex, high age, low level of education and who were divorced, separated or a widow/widower had a higher prevalence of SOL+WASO+EMA-insomnia compared to their respective demographic counterparts. The prevalence of possible anxiety, possible depression and use of hypnotics were higher among participants with SOL+WASO+EMA-insomnia compared to the other insomnia subtypes. The combination of WASO- and EMA-insomnia (WASO+EMA-insomnia) was associated with the most frequent alcohol consumption. Conclusion: Our findings suggest that there are major differences between the insomnia subtypes, both regarding demographics, but also in terms of how the complaints may affect daily life. Participants with combinations of SOL, WASO and EMA were more likely than participants with the other subtypes to have possible anxiety and possible depression, high alcohol consumption and to use hypnotics.